Fungal cell membrane-promising drug target for antifungal therapy - Sant, D. G.; Tupe, Santosh Genba; Ramana, Chepuri V.; Deshpande, Mukund V. (Journal of Applied Microbiology, 2016)
Increase in invasive fungal infections over the past few years especially in immunocompromised patients prompted the search for new antifungal agents with improved efficacy. Current antifungal armoury includes very few effective drugs like Amphotericin B; new generation azoles, including voriconazole and posaconazole; echinocandins like caspofungin and micafungin to name a few. Azole class of antifungals which target the fungal cell membrane are the first choice of treatment for many years because of their effectiveness. As the fungal cell membrane is predominantly made up of sterols, glycerophospholipids and sphingolipids, the role of lipids in pathogenesis and target identification for improved therapeutics were largely pursued by researchers during the last few years. Present review focuses on cell membrane as an antifungal target with emphasis on membrane biogenesis, structure and function of cell membrane, cell membrane inhibitors, screening assays, recent advances and future prospects.